Changes in wood properties of chestnut wood structural elements with natural aging - Topaloglu, Elif; Ustaomer, Derya; Ozturk, Murat; Pesman, Emrah (Maderas. Ciencia y Tecnología, 2021)
Knowing the effects of natural aging on wood properties is important both for the conservation of historical wooden material and for reuse of aged wood. The aim of this study was to investigate the wood properties of old wooden elements not impregnated with any protective chemicals and taken from different parts of Zeytinlik houses in Giresun, Turkey. Test samples were prepared from old wooden elements and freshly cut chestnut timber. The anatomical, chemical, physical and mechanical properties were determined according to standard procedure, and the results were compared with those of recent wood specimen. As a result of the anatomical identification, it was determined that the wooden elements used in traditional Zeytinlik houses belong to species of Anatolian chestnut (Castanea sativa), and after an average service life of 88, 113 and 120 years, there was no change in the anatomical structure of the old wooden elements. Fourier transform infrared band characterization of old wood specimens revealed that hemicelluloses degraded and lignin structure changed on the surface of almost all specimens. Especially, the wood density values of the facade elements were smaller than that of recent wood specimen. Except for the modulus of rupture of window sill and rafter, all mechanical properties were significantly greater compared with those of recent wood specimen. The results of this research showed that old wood not damaged by fungi and insects could be evaluated for reuse.